Enhancing Inclusion, Diversity, Equity and Accessibility (IDEA) in Open Educational Resources (OER) - Andersen, Nikki (Open textbook library., 2022)
This practical guide provides a framework and tips to enhance inclusion, diversity, equity, inclusion and accessibility in Open Educational Resources.